أهمية العمل وضرورة الفن - برهم لطفيّة; غريب يوسف (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
وقع اختياري على هذا البحث ، وهو أهمية العمل وضرورة الفن ، لما وجدت من اختلاف في المواقف والرؤى تجاه العلاقة بين الفن والعمل ، وحدود كل منها ، واختلاف في المواقف والرؤى تجاه فاعلية الفن وحضوره في الواقع الحياتي وبقي الاختلاف قائماً عبر مراحل التطور التاريخي ، إذ كان الفصل بين الفن والحياة تارة، والربط بينهما تارة أخرى ، تبعاً للقائلين ، ولمكوناتهم وتأثيراتهم ومواقفهم الفكرية عامة . والبحث في منطلقه يؤمن بالربط التلازمي بينهما ويرى أن هذا الربط حقيقة لا تقبل الجدال ولاسيما أن الفن نشاط إنساني مميز ، أو ممارسة عملية ، يستعين بها الإنسان لمواجهة الضرورات الخارجية . والقول بـ " العمل " يحفل بالخلق والإبداع، مما يجعل التجربة الفنية نابضة بالحياة والحركة. وجلّ ما أتوخاه ، من هذا البحث ، هو أن يستطيع المطّلع عليه التعرف على طبيعة العلاقة بين الفن والعمل، وطبيعة العلاقة بين الإنسان وكل منهما ، وأن تتكون لديه صورة لأهمية العمل وضرورة الفن في الواقع الحياتي، ولا سيما في مواجهة حالات الاستلاب والتشيؤ ، والثقافة الاستهلاكية . I have chosen this research, which is the importance of work and the necessity of art, for I have found a difference in visions and attitudes towards the relationship between art and work and the limits of each of them, as well as a difference in visions and attitudes towards the efficiency of art and its presence in everyday reality. The difference remained active throughout the stages of historical revolution, as there was sometimes the separation between art and life, and the connection between them some other times. That related to people’s beliefs and their intellectual attitude. This research, in essence, believes in connecting between them, and regards this connection as uncontroversial fact. This is especially because art is a distinct human activity or a unique human activity through which man faces the external necessities and claims that the "work" is rich in creation and creativity, making the artistic experience full of life and motion . What I am aiming at in this research is to get the reader acquainted with the nature of the relationship between art and work, and the nature of the relationship between man and each one of them, as well as to form a picture of the importance of work and the necessity of art in everyday reality, especially in confronting appropriation, thingification and consumerism.